Հայերենի եւ թալիշերենի ձեւաբանական մի ընդհանրության շուրջ (թալիշերենի Անբարանի բարբառի նյութի հիման վրա) - Հակոբ Ավչյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена анализу образования настоящего времени изъявительного наклонения в анбаранском диалекте талышского языка в сравнении с талышскими диалектами Азербайджанской Республики и армянским языком. This article analyzes the formation of the present indicative tense in Anbaran dialect of the Talyshi language in comparison with the Talyshi dialects spoken in the Republic of Azerbaijan and the modern Armenian language.
Keywords: Language and Literature